The shopping experience: ethnographies of black female consumption - Khoza, Gugulethu (My University, 2016)
“Come on, you know this shirt will look so good with that pair of blue jeans you bought the other week?” This mannequin says to me, or at least I am imagining that she is talking to me, let alone trying to convince me to buy this white shirt. She stands in the middle of the entrance of the shop next to her male companion that I assume is also trying to trick other men into buying the chino pants and collared shirt that he is wearing. I know that I just have to walk past and go over to get my prescription refill at the pharmacy located upstairs. Flash forward to an hour later, and I have gotten my prescription from the pharmacy, I even had some time to stop and buy a salad at the café. Something in my other hand feels a little heavier. Is that? Oh shoot! It’s a shopping bag; in it, the white shirt and a pair of black heels. I seem to have completely ignored the fact that I went into the shop and bought the white shirt! As I was making my way to go and pay for it, the mannequin told me how that black pair of heels would tie the outfit in together with my blue jeans and this white shirt. I notice a few other women with shopping bags and seemingly happy as they move around the aisles of the mall; I am these women. A young and black middle class female in a shopping mall that has just made a purchase from money she earned from work. This is what drew me into this topic; understanding the shopping experience that encompasses ideas around shopping and consumption practices as a black woman in post-apartheid South Africa. Specifically, shopping for luxury goods;